The production of Hindu-Muslim violence in contemporary India - Brass, Paul R. (Jackson School publications in international studies, 2003)
"Chronic Hindu-Muslim rioting in India has created a situation in which communal violence is both so normal and so varied in its manifestations that it would seem to defy effective analysis. Paul R. Brass, one of the world's preeminent experts on South Asia, has tracked more than half a century's riots in the north Indian city of Aligarh.